Sterlet, as a Valuable Resource for Food Production - Antonenko, Alina; Kireeva, Irina (Agrobiodiversity for Improving Nutrition, Health and Life Quality, 2017)
The article is devoted to the analysis of the productive indicators of sterlet females during the spawning campaign on the stretch of the practice at Fortuna-XXI. The paper used the conventional fish farming methods of the study. Stimulation of the maturation of sexual products of sires conducted by ecological and physiological methods with a single injection of synthetic drugs “surfahon“ and their subsequent aging under controlled conditions. Getting of sex products – by method Podushka S. “Analysis breeding and biological results of the 2nd round of spawning in PE “Fortuna – XXI“” – showed that females sterlet quantitative research individual reproductive rates differ slightly. Only females number 4 of the maximum body weight observed the dependence of the basic reproductive performance of this indicator. For round 2 breeding operations received 3.5 kg of caviar, fertilization rate which was 75%, in line with regulatory requirements. Overall, spawning with females of sterlet experimental group was satisfactory. Plan on getting sexual products of sterlet is 80%.